2018
DOI: 10.1021/acs.jpcc.8b00569
|View full text |Cite
|
Sign up to set email alerts
|

A High-Capacity Lithium–Gas Battery Based on Sulfur Fluoride Conversion

Abstract: Identification of novel redox reactions that combine the prospects of high potential and capacity can contribute new opportunities in the development of advanced batteries with significantly higher energy density than today's state of the art, while advancing current understanding of nonaqueous electrochemical transformations and reaction mechanisms. The immense research efforts directed in recent years towards metal-gas, and in particular lithiumoxygen (Li-O 2 ) batteries, have highlighted the role that gas-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
(114 reference statements)
0
25
0
Order By: Relevance
“…Examples of electrochemical hybrid capture and utilization is the electrochemical seawater battery system [176], the alkali metal-based CO 2 batteries (e.g., lithium-CO 2 batteries [177,178]) and electrochemical CO 2 capture and conversion combinations [25,[179][180][181][182][183]. The absence of pH-swings, and the lack of further development of these proposed electrochemical capture routes, categorizes these concepts beyond the scope of this review.…”
Section: Molten Carbonate Cells and Hybrid Electrochemical Capture Mementioning
confidence: 99%
“…Examples of electrochemical hybrid capture and utilization is the electrochemical seawater battery system [176], the alkali metal-based CO 2 batteries (e.g., lithium-CO 2 batteries [177,178]) and electrochemical CO 2 capture and conversion combinations [25,[179][180][181][182][183]. The absence of pH-swings, and the lack of further development of these proposed electrochemical capture routes, categorizes these concepts beyond the scope of this review.…”
Section: Molten Carbonate Cells and Hybrid Electrochemical Capture Mementioning
confidence: 99%
“…Our own recent efforts have shown that gas cathode reactions need not be limited to common O 2 , CO 2 or SO 2 , but can also involve nominally ‗inert', highly fluorinated gases. 12 The present work explores the viability of a highly-fluorinated gas, nitrogen trifluoride (NF 3 ), as a gas cathode in a Li battery. NF 3 is a colorless, nonflammable gas with routine usage in the microelectronics industry.…”
Section: Toc Graphicmentioning
confidence: 99%
“…Among various solid cathode materials, fluorinated carbon (CF x ) has attracted unprecedent attention due to their high theoretical energy density, which is much higher than that of lithium ion batteries (~500 W h kg −1 ) [3]. To fill this short-term technology gap for producing batteries with higher energy densities, several types of nonaqueous metal-gas batteries have been explored to meet growing demands, such as Li-O 2 [4], Na-O 2 [5], K-O 2 [6], Li-CO 2 [7,8], Li-NF 3 [9], and Li-SF 6 [10][11][12]. However, the gas-to-solid conversion reaction involves a solution-mediated electrochemical process that induces complex thermodynamics, kinetics, and transport considerations, and it remains a challenge to achieve the potential energy densities and realize practical applications for these systems.…”
Section: Introductionmentioning
confidence: 99%